Study on Land Control Settlement in the Framework of Forest Area Arrangement (PPTPKH) in Banyuwangi Regency - Sirajuddin, Muhammad Munif (Marcapada: Jurnal Kebijakan Pertanahan, 2024)
Legally, land ownership rests on a solid foundation. Land ownership gives the rightholder the authority to control, use, and benefit from the land. In Indonesia, land ownership predates the area's designation as a forest area. Regulations and patterns of land ownership settlement have undergone numerous changes over time. Law No. 11 of 2020, which pertains to job creation and its related regulations, represents a significant advancement in agrarian reform, particularly in Java, with a particular focus on items originating from forest regions. This paper employs a qualitative research method, combining a descriptive and normative legal approach with a comparative analysis of the regulations. This method employs techniques such as observation, interviews, and document studies, along with a com-parison of regulations. This paper aims to investigate the implement¬tation of agrarian reform, combined with a comparison before and after the enact-ment of the Job Creation Law. An important finding is that Java, especially Banyuwangi Regency, East Java Province, can carry out this activity. The settlement pattern uses a forest area release scheme and social forestry. In conclusion, after the UUCK (Job Creation Law) is issued, Java, Bali, and Lampung can implement PPTPKH. The state protected agricultural plots with legal permits under the Social Forestry scheme, and redistributed 10,323 plots of land in forest areas to the community.